Théophile de Viau 1914 : anthologie et appropriation - Maxime Cartron (Revue Italienne d'Etudes Françaises, 2019)
This paper analyzes a poetic anthology of Théophile de Viau published in 1914 with woodcuts. Starting from a study of the editorial context and the publication stakeholders, the purpose aim to prove that the choice and the texts arrangement, combined with the illustrations, consecrate the inscription of Théophile’s work in History, and thus constitutes a modality of his appropriation and instrumentalisation for ideological goals.